1985
DOI: 10.1073/pnas.82.23.7994
|View full text |Cite
|
Sign up to set email alerts
|

Human group-specific component (Gc) is a member of the albumin family.

Abstract: The group-specific component (Gc) is the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

1987
1987
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(50 citation statements)
references
References 25 publications
0
49
0
1
Order By: Relevance
“…Numerous studies detected DBP bound to the surface of several cell types, including human macrophages and lymphocytes, supporting the concept that direct substrate trafficking is pivotal in vitamin D 3 regulation (35)(36)(37). Therefore, we studied DBP uptake in CD4 + T cells and macrophages isolated from male and female MS patients.…”
Section: Gender Influence On Vitamin D 3 Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies detected DBP bound to the surface of several cell types, including human macrophages and lymphocytes, supporting the concept that direct substrate trafficking is pivotal in vitamin D 3 regulation (35)(36)(37). Therefore, we studied DBP uptake in CD4 + T cells and macrophages isolated from male and female MS patients.…”
Section: Gender Influence On Vitamin D 3 Metabolismmentioning
confidence: 99%
“…DBP is a serum glycoprotein that binds and transports vitamin D 3 and its metabolites to target cells (75). Human DBP has been linked to several membrane components of peripheral blood monocytes, lymphocytes, and neutrophils, supporting the concept of a cell surface-binding site for DBP (35)(36)(37). In addition, studies demonstrated that in vivo endocytic uptake of the vitamin D 3 -DBP complex is mediated by megalin and cubilin, two members of the low-density lipoprotein-like receptor protein family (76,77).…”
Section: Foxp3mentioning
confidence: 99%
“…The most characteristic feature of the albumin sequence is the repetitious pattern of 17 disulfide bridges that organizes the molecule into three homologous, yet distinct, domains. With the cDNA cloning and sequencing of alpha-fetoprotein (human : Law & Dugaiczyk, 1981;Moringa et al, 1983;rat: Jagodzinski et al, 198 1;mouse: Gorin et al, 1981) and vitamin D-binding protein (human: Yang et al, 1985;Schoentgen et al, 1986;rat: Cooke & David, 1985;mouse: Yang et al, 1990), it became evident that these proteins are related to albumin through a series of gene duplications. As such these proteins provide an interesting glimpse into the evolution of a multigene family.…”
mentioning
confidence: 99%
“…Recently, the relationship between the risk of chronic obstructive pulmonary disease (COPD) and the Gc protein allele type, such as Gc*1F, Gc*1S, Gc*2, had been reported. [93][94][95][96][97] Gc*1F increased the COPD risk, while Gc*2 suppressed the risk. Thus, the allele type of Gc protein is an important factor in COPD.…”
Section: Discussionmentioning
confidence: 99%